Implementation of UKBI to improve students’ listening ability - Handara Tri Elitasari; Ali Mustadi; M. Fakhrur Saifudin (Intelektual Pustaka Media Utama, 2019)
Listening is one of the basic language skills that must be possesed by student in elementary teacher education study program. As a teacher candidates, listening ability can be used as knowledge for student in teaching practice in elementary school. The listening ability is still relatively low. Listening ability for students its important, so need a have efforts and attention.This study aims to improve the students listening ability through the implementation of UKBI. UKBI is a proficiency test of Indonesian language that used as a method to measured proficiency of someone’s language ability. This study used classroom action research with two cycles. This study was conducted on 41 students class 2 A of elementary teacher education student in Ahmad Dahlan University. Data collection methods was used test and observation. The results showed that the implementation of UKBI can improve the listening ability to elementary teacher education student. This was proved in cycle I and cycle II with the increase of the average listening scores of 75.12 and 83.05 and the classical completeness of 78.05% and 90.24%. Analysis of the listening scores showed that remembering is the most prominent ability among understanding and analyzing.